On periodic and bounded solutions of the operator Riccati equation - Dorogovtsev, A. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Sufficient conditions for the existence of periodic and bounded solutions of the operator Riccati equation are presented.